2015
DOI: 10.1097/iae.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging of Gunn's Dots

Abstract: Gunn's dots are highly anisotropic structures close to the inner limiting membrane. Their density, size, and age-related decline are closer to the characteristics of hyalocytes than those of Müller cells. Further studies are necessary to progress in the determination of their origin and interest as biomarkers of retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
2
12
1
Order By: Relevance
“…26 They can appear as disc-shaped collagenous membranes covering the fovea, or may form a ring along the foveal margin, or may develop a cyst-like structure. 31,32 In contrast to Nakamura et al, 28 Gandorfer et al 30 attributed the hyperreflective knobs, detected with SD-OCT and identified after incomplete ILM peeling in eyes with macular holes, to remnants of vitreous fibrils adherent to the basal lamina of the ILM and not fibroproliferation of the ILM. In young patients, persistence of the posterior hyaloid or vitreous remnants may explain the presence of hyperreflective dots in the absence of a PVD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…26 They can appear as disc-shaped collagenous membranes covering the fovea, or may form a ring along the foveal margin, or may develop a cyst-like structure. 31,32 In contrast to Nakamura et al, 28 Gandorfer et al 30 attributed the hyperreflective knobs, detected with SD-OCT and identified after incomplete ILM peeling in eyes with macular holes, to remnants of vitreous fibrils adherent to the basal lamina of the ILM and not fibroproliferation of the ILM. In young patients, persistence of the posterior hyaloid or vitreous remnants may explain the presence of hyperreflective dots in the absence of a PVD.…”
Section: Discussionmentioning
confidence: 97%
“…In young patients, persistence of the posterior hyaloid or vitreous remnants may explain the presence of hyperreflective dots in the absence of a PVD. 31 Paques et al 32 described Gunn dots using en face adaptive optics and speculated that these either represented Müller cell end feet or vitreous hyalocytes. However, the unique location in the foveola, the larger dimension, the three-dimensional appearance on B-scan, and the absent detection on fundoscopy indicate that the hyperreflective dots identified in our study are not Gunn dots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it has been shown that extracting the asymmetric component of photoreceptor reflectance (split-detection 27 ) is a powerful means for the identification of cones in a dystrophic retina. The Henle fibers, [28][29][30] the nerve fiber layer, 31 and Gunn's dots 32 also show strong directional reflectance; hence, multiangle imaging appears as a necessary procedure for adequate interpretation of high-resolution retinal imaging.…”
Section: Discussionmentioning
confidence: 99%